Exploring the Link between Mentoring Program Structure & Success Rates: Results from a National Survey - Miller, J. Mitchell (American journal of criminal justice, 2013)
Though mentoring has emerged as a promising and low-cost intervention for at-risk youth in recent years, the scientific knowledge base on the topic remains under-developed. The current study augments the knowledge base on youth mentoring by analyzing programmatic elements of mentoring programs situated in or adjacent to the juvenile justice system that are predictive of participant success. Poisson regression was utilized to analyze data collected through a national mentoring community saturation survey. Findings indicated that mentoring programs that require more frequent interaction and sustain relationships for longer timeframes realize higher success rates. Similarly, the use of formal mentor training was also observed as indicative of the use of evidence based practices and higher success rates, though likely beyond the logistical and fiscal reach of some local mentoring initiatives. The implications for further research and the mentoring community are discussed.